Transplantation of mesenchymal stem cells for prevention of acute myocardial infarction induced heart failure: study protocol of a phase III randomized clinical trial (Prevent-TAHA8) - Armin Attar; Ahmad Monabati; Mohammad Montaseri; Massoud Vosough; Seyed Ali Hosseini; Javad Kojouri; Alireza Abdi-Ardekani; Peyman Izadpanah; Negar Azarpira; Gholamreza Pouladfar; Mani Ramzi (Trials, 2022)
Abstract Background Results from recent clinical trials on bone marrow mononuclear cell (BM-MNC) transplantation show that this intervention can help reduce the incidence of heart failure (HF) after acute myocardial infarction (AMI). However, no study has evaluated the effect of the transplantation of mesenchymal stem cells (MSCs) on a clinical endpoint such as HF. Methods This single-blinded, randomized, multicenter trial aims to establish whether the intracoronary infusion of umbilical cord-derived Wharton’s jelly MSCs (WJ-MSCs) helps prevent HF development after AMI. The study will enroll 390 patients 3 to 7 days following AMI. Only patients aged below 65 years with impaired LV function (LVEF < 40%) will be included. They will be randomized (2:1 ratio) to either receive standard care or a single intracoronary infusion of 107 WJ-MSCs. The primary outcome of this study is the assessment of HF development during long-term follow-up (3 years). Discussion Data will be collected until Nov 2024. Thereafter, the analysis will be conducted. Results are expected to be ready by Dec 2024. We will prepare and submit the related manuscript following the CONSORT guidelines. This study will help determine whether or not the infusion of intracoronary WJ-MSCs in patients with AMI will reduce the incidence of AMI-induced HF. Trial registration ClinicalTrials.gov NCT05043610 , Registered on 14 September 2021 - retrospectively registered.